1994
DOI: 10.1002/macp.1994.021950803
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of amphiphilic “dumbbell”‐shaped grafted block copolymers, 1. Anionic synthesis via a polyfunctional initiator

Abstract: Two poly(ethy1ene oxide) stars linked by a long polystyrene chain represent a novel amphiphilic architecture (dumbbell), which is available by anionic grafting of ethylene oxide from a hydroxylated polybutadiene-block-polystyrene-block-polybutadiene triblock copolymer. The short butadiene end-blocks (DP, = 36) of a BSB triblock copolymer with a long styrene middle block (DP, = 650) was first modificd by hydroboration and oxidation. A multifunctional alkoxide initiator is thus prepared by titration of the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 20 publications
2
51
0
3
Order By: Relevance
“…Moreover, they are of theoretical relevance for studying principles of macromolecular self-assembly [6][7][8][9][10][11][12][13][14][15][16]. Several studies on the solution behavior of amphiphilic ABC triblock copolymers have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they are of theoretical relevance for studying principles of macromolecular self-assembly [6][7][8][9][10][11][12][13][14][15][16]. Several studies on the solution behavior of amphiphilic ABC triblock copolymers have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…branched topologies, [44][45][46] with a focus on linear ABC triblock copolymers, [47][48][49][50][51][52][53][54] which actually started with their use as compatibilizers in a polymer blend. [55][56][57] While he declined an offer from the Leibniz-Institut für Polymerforschung Dresden in 1994, he accepted an offer from the Universität Bayreuth and became full professor in Macromolecular Chemistry in 1997, where he stayed for the remainder of his career.…”
Section: Doi: 101002/macp201900370mentioning
confidence: 99%
“…[q] limiting viscosity numbers The p parameter corresponds to the ratio of the geometrical defined radius of gyration (R,) and to the hydrodynamic radius (Rh) which is defined through the Stockes-Einstein relation and D (cm' s-') corresponds to the translational diffusion coefficient measured in toluene p = R, / Rh and R h = kT / (6qoD), Anionic copolymerization of macromonomers "Dumbbell" polymers containing a central PS block linking two branched PEO's have been prepared recently (Ref. 15) and were shown to exhibit typical properties of amphiphiles Fig.3. Schematic representation of the structures of branched polymers based on macromonomers They were prepared from triblock copolymers containing terminal hydroxylated segments We have developed another approach to prepare such "dumbbell" species or "palmtree" polymers ( Fig 3) based on anionic homopolymerization of macromonomers The anionic polymenzation of a monofunctional or bifunctional living polystyrene chain was conducted first The carbanionic chain ends served thus as initiator for the anionic polymerization of the a-methacryloyloxy PS macromonomer An example is given on tab 5 In spite of the fact that the molar mass distribution of the precursor chain is rather large, the molar mass of this "palmtree" polymer corresponds to the expected value The calculated value for the DP, of the polymacromonomer @P, =5) is close to the measured value…”
Section: Solution Propertiesmentioning
confidence: 99%